Cognitive deficits in mice lacking Nsun5, a cytosine‐5 RNA methyltransferase, with impairment of oligodendrocyte precursor cells. Issue 4 (28th November 2018) - Zhang, Tingting; Chen, Peipei; Li, Wei; Sha, Sha; Wang, Ya; Yuan, Zihao; Shen, Bin; Chen, Ling
Abstract: Williams‐Beuren syndrome (WBS) is a microdeletion disorder with cognitive phenotype. NSUN5 gene, which encodes a cytosine‐5 RNA methyltransferase, is located in WBS deletion locus. To investigate the influence of NSUN5 deletion on cognitive behaviors, we produced single‐gene Nsun5 knockout ( Nsun5 ‐KO) mice. Here, we report that adult Nsun5 ‐KO mice showed spatial cognitive deficits. Size of the brain and hippocampal structures and the number of CA1 or CA3 pyramidal cells in Nsun5 ‐KO mice did not differ from WT mice. Basal properties of Schaffer collateral‐CA1 synaptic transmission in Nsun5 ‐KO mice were unchanged, but NMDA receptor (NMDAr)‐dependent long‐term potentiation (LTP) was not induced. The NMDA‐evoked current in CA1 pyramidal cells was reduced in Nsun5 ‐KO mice without the changes in expression and phosphorylation of NMDAr subunits NR2A and NR2B. Although the protein level of AMPA receptor subunit GluR2 was attenuated in Nsun5 ‐KO mice, the AMPA‐evoked current was not altered. Hippocampal immuno‐staining showed the selective expression of Nsun5 in NG2 or PDGFRα labeled oligodendrocyte precursor cells (OPCs), but not in pyramidal cells or astrocytes. Analysis of RT‐PCR determined the Nsun5 expression in purified populations of OPCs rather than neurons or astrocytes. The Nsun5 deficiency led to decreases in the number and neurite outgrowth of OPCs in the hippocampal CA1 and DG, with the decline in NG2 expression and OPCs proliferation. These findings indicate that the Nsun5 deletion suppresses NMDAr activity in neuronal cells probably through the disrupted development and function of OPCs, leading to deficits in NMDAr‐dependent LTP and spatial cognitive abilities. Main Points: Nsun5, a cytosine‐5 RNA methyltransferase, is expressed in NG2‐positive oligodendrocyte precursor cells (OPCs). Nsun5 knockout in mice causes deficits in spatial cognition and hippocampal LTP with impairment of OPCs and dysfunction of NMDA receptor.